Perbedaan Pola Pikir dan Adaptasi Mahasiswa Baru Prodi Akuntansi berdasarkan Latar Belakang Pendidikan yang Berbeda - Nabila, Putri Ayu; Andriani, Rizka Putri; Muthmainah, May Hayati; Putri, Dekana Melani (CV. Kalimasada Group, 2025)
The problems faced by new students of the Accounting Program are enrolling from diverse educational backgrounds without considering their readiness to grasp fundamental accounting concepts can potentially lead to difficulties in keeping up with coursework. This research article aims to analyze the influence of educational background and learning readiness on the understanding of basic accounting concepts among freshmen, based on their educational backgrounds. Using a descriptive qualitative approach, this study examined 30 new students (10 male, 20 female) from various educational backgrounds (SMK Accounting, High School IPS, High School IPA, and Islamic Boarding School/MA) at UIN Syarif Hidayatullah Jakarta. Research results show variations in the understanding of basic accounting concepts influenced by educational background; students from Accounting Vocational School and IPS High School demonstrate faster comprehension compared to students from non-economic backgrounds. This disparity highlights the significance of differentiated learning and guidance strategies to ensure the academic success of all students.